EFFECT OF DUKEM INHIBITOR ON AISI 1010 IN THE SECONDARY COOLING SYSTEM OF RSG GAS - Rahayu Kusumastuti; Sumaryo Sumaryo; Sriyono Sriyono (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2018)
The secondary coolant of RSG GAS is an open system whose components are easy to interact with oxygen from surrounding environment to initiate corrosion. Corrosion controls are usually done by adding inhibitors. Dukem inhibitors are one alternative substitute inhibitor that may be used in the secondary cooling system of RSG GAS. The purpose of this study is to find out the optimum dukem concentration that needs to be added to RSG GAS secondary cooling system and to understand the interaction phenomenon between dukem inhibitors and AISI 1010 material. The analysis of orthophospat content as an active compound in dukem inhibitors is done by FTIR and UV-vis spectrophotometer. The phenomenon of interaction between inhibitors and material is studied by FTIR, SEM and XRD. Corrosion test with potentiostat is performed to assess the optimal concentration of dukem inhibitor which should be added. From the results of FTIR analysis, it is known that the active compounds in dukem inhibitors are ortho-phosphate. The analysis using UV-vis spectrophotometer showed that orthophospat concentration is 4.2 ppm. The SEM analysis demonstrated the presence of an inhibitor layer, which is capable of masking the surface porosity. The AISI 1010 material has better corrosion resistance when inhibitor was injected to the coolant of 150 ppm. The corrosion rate decreased by by 45.20% from 10.95 mpy to 6.02 mpy. The type of dukem inhibitor is mixed type inhibitor. Visually, corrosion product was not formed in the AISI 1010 surface during immersed in the inhibitor solution but it is clearly adhered on surface when immersed in solution added by inhibitors. It can be concluded that dukem inhibitors can be used as inhibitors in RSG GAS secondary cooling systems.Keywords: dukem, inhibitor, corrosion, secondary cooling system, RSG GAS. PENGARUH INHIBITOR DUKEM terhadap proses korosi pada SISTEM PENDINGIN SEKUNDER RSG GAS. Sistem pendingin sekunder RSG GAS merupakan sistem pendingin resirkulasi terbuka. Komponen pendingin ini mudah berinteraksi dengan udara luar yang mengandung banyak oksigen sehingga dapat mempercepat proses korosi. Salah satu cara pengendalian korosi adalah dengan penambahan inhibitor. Inhibitor dukem merupakan salah satu alternatif inhibitor pengganti yang dapat di gunakan pada sistem pendingin sekunder. Tujuan dari penelitian ini adalah untuk mengetahui konsentrasi penambahan dukem yang optimal ke pendingin sekunder RSG GAS dan untuk mengetahui fenomena interaksi inhibitor dukem terhadap material AISI 1010. Analisis kandungan ortophospat sebagai senyawa aktif pada inhibitor dukem dilakukan dengan FTIR dan spektrofotometer uv-vis. Fenomena interaksi antara inhibitor dengan material di lakukan dengan analisis FTIR, SEM dan XRD. Uji korosi dengan potensiostat akan memberikan informasi konsentrasi optimium inhibitor dukem dan tipe inhibitor yang sebaiknya di gunakan. Dari hasil analisis FTIR diketahui bahwa kandungan senyawa aktif pada inhibitor dukem adalah senyawa orto-phospat. Analisis menggunakan spektrofotometer uv-vis memperoleh kadar ortophospat sebesar 4,2 ppm. Analisis SEM menunjukkan adanya lapisan inhibitor yang mampu menutupi porositas (spheroid) pada permukaan AISI 1010. Analisis XRD menunjukkan adanya komposisi produk korosi oksida FeO(OH) pada permukaan AISI 1010 jika tidak ditambahan inhibitor. Material AISI 1010 mempunyai ketahanan terhadap korosi yang lebih baik ketika inhibitor ditambahkan ke dalam pendingin sebesar 150 ppm. Hal ini terlihat dari penurunan kecepatan laju korosi sebesar 45,20% dari 10,95 mpy menjadi 6,02 mpy. Analisis tafel menunjukkan inhibitor dukem merupakan jenis inhibitor campuran. Secara visual, produk korosi tidak terbentuk pada permukaan AISI 1010 ketika direndam dalam larutan inhibitor sedangkan produk korosi terlihat jelas pada specimen tanpa inhibitor. Dari penelitian ini dapat ditarik kesimpulan bahwa inhibitor dukem dapat digunakan sebagai inhibitor pada sistem pendingin sekunder RSG GAS. Kata Kunci : dukem, inhibitor, korosi, pendingin sekunder, RSG GAS